Analysis of Survival Rates of Patients Diagnosed With Incipient Esophagic Cancer - Mauad, Edmundo Carvalho (World J Oncol, 2010)
BACKGROUND: Esophagic cancer incidence is extremely variable worldwide. Also, the global survival rate has not oscillated significantly since last decade. Most of the worse prognoses are found among patients with advanced stages. Despite that, around 10% of cases occur in patients with initial stage, which strongly associate these patients with unfavorable prognosis. We sought to analyze the impact of time free of disease and global survival rates of patients with initial stage of esophagic cancer. METHODS: We studied 18 patients with initial stage of esophagic cancer (stage 0 and I), examined and treated at Hospital de Cancer de Barretos between 1990 and 2005. RESULTS: The vast majority of patients were male (83.3%) with age up to 49 yarest old (77.8%), squamous cell carcinoma (SCC) (88.9%) and stage I (83.3%). Most of them were smoker (60.0%) and etilist (62.5%). There were 38.9% of the patients with comorbities like dysphagia and epigastralgia correlated to other pathological conditions. We found free disease rates of 100% and 82.5%, respectively for 12 and 36 months. The significant prognostic evidence was the age, epigastralgia symptoms and chemotherapy. From 18 patients, 6 passed away during the period of 36 months follow up due to cancer consequences. The probabilities of global survival were 76.7% and 64.4% after 12 and 36 months, respectively, and none of the analyzed variables influenced in theses rates. CONCLUSIONS: Our data ratifies those from previous reported. The global survival rates were worse than reported by literature, maybe in consequence of the poor clinical condition of many patients which limited the option for more aggressive therapy.